Bactericidal activities of DU-6859a and clinafloxacin (CI-960) against staphylococci. - Forstall, G J (1994)
Time killing curves were calculated at concentrations of 2 and 8 times the MICs of DU-6859a and clinafloxacin against six isolates of Staphylococcus aureus. Both quinolones produced a decrease in the log10 CFU per milliliter of > or = 3 within 3 h at 2 and 8 times the MIC for the ciprofloxacin-susceptible isolates and at 8 times the MIC for the ciprofloxacin-resistant isolates; however, only 8 times the MIC of DU-6859a consistently prevented regrowth of all isolates after 24 h of incubation.